2015
DOI: 10.1007/s12088-015-0539-3
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Profiling and Diversity of Bacterial Communities in the Death Valley, an Extreme Habitat in the Atacama Desert

Abstract: The Atacama Desert, one of the driest deserts in the world, represents a unique extreme environmental ecosystem to explore the bacterial diversity as it is considered to be at the dry limit for life. A 16S rRNA gene (spanning the hyper variable V3 region) library was constructed from an alkaline sample of unvegetated soil at the hyperarid margin in the Atacama Desert. A total of 244 clone sequences were used for MOTHUR analysis, which revealed 20 unique phylotypes or operational taxonomic units (OTUs). V3 regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
(56 reference statements)
0
9
0
1
Order By: Relevance
“…The case of Bacillus spp. is worth mentioning, as species of this genus are among the first and one of the most common type of bacteria reported in Yungay 27,65,66 and also in other sites of the hyperarid core of the Atacama [67][68][69] .…”
Section: Resultsmentioning
confidence: 96%
“…The case of Bacillus spp. is worth mentioning, as species of this genus are among the first and one of the most common type of bacteria reported in Yungay 27,65,66 and also in other sites of the hyperarid core of the Atacama [67][68][69] .…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies using culture-dependent methods have reported low numbers of bacteria in Atacama Desert soils, ranging from not detectable to 10 6 CFU per g of soil, with a high degree of spatial heterogeneity ( Crits-Christoph et al, 2013 ). Analysis through culture-independent methods on the subsurface layers of the hyper-arid core showed limited abundance of microbial communities including Proteobacteria, Actinobacteria, Cyanobacteria, Chloroflexi, Firmicutes, Gemmatimonadetes , Planctomycetes , and Thermomicrobia phyla ( Dong et al, 2007 ; Crits-Christoph et al, 2013 ; Azua-Bustos et al, 2015 ; Piubeli et al, 2015 ; Azua-Bustos et al, 2017 ).…”
Section: Microbes In Dry Environmentsmentioning
confidence: 99%
“…From the deepest seafloor to the top of the highest mountain, or the hottest desert to the coldest Antarctic plain, microorganisms have been recovered. Extreme habitats can support diverse bacterial communities [18,[75][76][77][78][79][80]. The investigation of the microbial communities which have managed to establish themselves under harsh conditions has helped further our understanding of how life evolved.…”
Section: Diversity Of Tellurite-resistant Microbes Inhabiting Extremementioning
confidence: 99%